Fibrin Gel Properties and Gelation Structures for Tissue Engineering Scaffold and Biomedical Engineering Applications - Vadival, G N; Sukmana, Irza; Risano, A Yudi Eka; Sugiri, Agus; Hamdani, Fadil (FTMD Institut Teknologi Bandung, 2023)
Fibrin gel is utilized in a wide range of medical applications, such as hemostatic agents, wound healing, drug delivery, cell delivery, cell differentiation, and tissue engineering. Notably, fibrin gel exhibits exceptional extensibility compared to other filamentous biopolymers, capable of stretching over five times its original length without breaking. Remarkably, it can fully recover from elongations exceeding 100% once the applied stress is removed. This paper presents an optimized formulation of fibrinogen and thrombin tailored for culturing human umbilical vein endothelial cells (HUVEC). We explore the mechanical and physical properties of the fibrin gel, aiming to identify ways to enhance its medical applications. The gel is synthesized in vitro through the combination of fibrinogen and thrombin, allowing us to assess how varying the proportions of these components affects the gel structures and properties